Application of phytosociological information in the evaluation of the management of protected areas - Pereña-Ortiz, Jaime Francisco; Salvo-Tierra, Ángel Enrique; Sánchez Mata, Daniel (MDPI, 2023)
The classification system of plant communities using phytosociological methods can be applied to their conservation in protected areas, as well as in establishing adequate protections and granting legal status to such areas. A new integrative index is developed to classify plant communities for the evaluation of the conservation status of protected areas, obtained from the product of three statistical indices of diversity: Syntaxonomic Distinctness, Rarefaction and Areas Prioritisation, which has been named DRA (acronym of the three indices used). The DRA is used to assess whether the status granted to Protected Areas matches the values provided by the plant communities within them and which were the basis for the identification and description of the Habitats of Community Interest (Habitats Directive—92/43/CEE). The proposed method was applied to the network of protected natural areas on the Andalusian coast, including 14 areas with different protection status, where, once the plant communities they contain were identified, the DRA index was applied to each of them and compared with the Legal Protection Index, i.e., the current protection regime; it becomes clear, objectively, that not all the statuses assigned, whether the IUCN criteria or those of the Andalusian government, correspond to the real levels of protection they should have on the basis of their plant communities.
Keywords: Asociaciones vegetales; Fitosociología; Plant communities; Syntaxonomic distinctness; Rarefaction; Conservation priority; Legal protection; Protected area